Individual, Social and Institutional Vulnerabilities in the Premature Infant Care at Home - Viera, Claudia Silveira; Pancieri, Leticia; da Silva, Rosane Meire Munhak; Wernet, Monika; Gaiva, Maria Aparecida Munhoz; de Mello, Debora Falleiros (Nova Southeastern University, 2022)
The prematurity carries some difficulties for families during the preterm infant hospitalization, as well as, after hospital discharge. In this context, is required a specific knowledge about the preterm biological characteristics, family's life conditions, health care, and social context. This study aims to analyze parent's experiences on daily home care for preterm infants focusing on individual, social and institutional vulnerabilities. Descriptive qualitative study was developed through the hermeneutic perspective approach, in South of Brazil with six families, who had babies discharged from Neonatal Intensive Care Unit. Non-structured interviews were recorded in the home visit with 12 participants (parents) and genogram and ecomap were applied. Emerged as core theme: Parents' feelings related to preterm care at home and their interaction with health services. During the first month after discharge, parents were emotionally vulnerable. There is a lack of connection between parents and Primary Health Care, what increases institutional vulnerability. After discharge, parents have experienced an individual, social, and institutional vulnerability. To minimize their institutional vulnerability, the health services need to be organized in a network offering qualified follow-up. Applying the Health Policy to care for premature infant, consequently, reducing the individual vulnerability and recognize social vulnerabilities related to premature infant care.
Keywords: Descriptive qualitative study; Parents; Preterm infant; Primary health care; Vulnerability